2012
DOI: 10.1530/erc-12-0129
|View full text |Cite
|
Sign up to set email alerts
|

Expression of guanylyl cyclase-B (GC-B/NPR2) receptors in normal human fetal pituitaries and human pituitary adenomas implicates a role for C-type natriuretic peptide

Abstract: C-type natriuretic peptide (CNP/Nppc) is expressed at high levels in the anterior pituitary of rats and mice and activates guanylyl cyclase B receptors (GC-B/Npr2) to regulate hormone secretion. Mutations in NPR2/Npr2 can cause achondroplasia, GH deficiency, and female infertility, yet the normal expression profile within the anterior pituitary remains to be established in humans. The current study examined the expression profile and transcriptional regulation of NPR2 and GC-B protein in normal human fetal pit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 54 publications
2
20
0
Order By: Relevance
“…CNP was first isolated from porcine brain23 and is distributed throughout the brain and pituitary682425. In the cardiovascular system, CNP is expressed in endothelial cells, where it acts as a vascular mediator regulating local vascular tone and growth9102627.…”
Section: Discussionmentioning
confidence: 99%
“…CNP was first isolated from porcine brain23 and is distributed throughout the brain and pituitary682425. In the cardiovascular system, CNP is expressed in endothelial cells, where it acts as a vascular mediator regulating local vascular tone and growth9102627.…”
Section: Discussionmentioning
confidence: 99%
“…This later gene has been demonstrated that is expressed exclusively in the Rathke's pouch and adenohypophysis during the development of pituitary in both chicken and mouse embryos and not in the neuroectoderm (Proszkowiec-Weglarz et al 2011). By using these expressions it could be concluded that all pituitary samples used as normal contained all five adenohypophophysis specific cell types (data not shown) [15][16][17][18]. Tumor tissue specimens were immediately frozen in liquid nitrogen after the adenoma removal, and stored at -80 o C until use.…”
Section: Samples and Rna Extractionmentioning
confidence: 99%
“…They act via cell surface receptors with intrinsic guanylyl cyclase activity termed NPR1 (GC-A) and NPR2 (GC-B). [695][696][697][698][699][700][701] Thus, the anterior pituitary contains the highest tissue concentration of CNP, and immunostaining revealed particularly strong expression in gonadotropes, 702 where it is found within secretory vesicles. 667,695 NPR1 is selectively activated by ANP and BNP, whereas NPR2 is selective for CNP, and all mediate elevation of cGMP levels in their target cells.…”
Section: Natruiretic Peptides Nitric Oxide and Guanylyl Cyclasesmentioning
confidence: 99%
“…ANP and BNP are well-characterized regulators of cardiac and renal function, but the physiological roles of CNP are less clear. 651,700,701 Although CNP does not stimulate LH secretion or modulate GnRH-stimulated LH secretion, 695,698,700 work with gonadotrope-derived cell lines reveals that it can stimulate the human αGSU promoter 700 and that GnRH may stimulate CNP expression (transcriptional regulation of the proximal Nppc gene). 342 Female mice with this deletion are also infertile, as are mice in which the gene encoding GC-B (Npr2) is deleted, and this is consistent with evidence supporting a role for CNP in the hypothalamo-pituitary-gonadal axis.…”
Section: Natruiretic Peptides Nitric Oxide and Guanylyl Cyclasesmentioning
confidence: 99%